An educational proposal to face the challenges of the european higher education area: international service learning experience in medicine and education of the University of Malaga, Spain - Cabello-Porras, María Rosario; Barquín-Ruiz, Francisco Javier (My University, 2017)
Higher Education need to be paced to world and society evolution and to technology and scientific advances. Specifically in Europe, in the last years, we had to adapt the curricula to the European Higher Education Area (EHEA). We have reached a high level of scientific and technycal competences but we detect, some lacks of time and tools to developed all the transversal competences and skills of the professionals profile that are demand by the present society in which exists glaring gaps and inequities, in particular in health, that need a responsable answer/action. Actually a “redesign of professional health education is necessary and timely, in view of the opportunities for mutual learning and joint solutions offered by global interdependence due to acceleration of flows of knowledge, techologies, and financing across borders and the migration of both professionals and patients” (Frenk et al 2010, Lancet). In the educational panorama, it has been possible to expand the training of future teachers in one year, the reduction of the number of students for groups to provide a more individualized teaching and the slight increase of the time of practicum. It is required to implemented an sostainable innovation in medical education to evolve a high quality medicine in all the areas and competences needed. Likewise, it seems necessary that student-teachers known spaces that are not properly school-based and have experiences in contexts of either informal education or with marginal groups outside of the standardized schooling. International Service Learning (ISL) has provided health professional students and tearches-students the opportunity to provide healthcare and education under the direction of trained faculty, to underserved populations in developing countries (Seifer SD et al1998. Acad Med). Objective: To verify the usefulness of SL experience as an educational methodology in higher education in order to support or not the modification of the current contents of the medical and education curricula and design new subjects based on SL in Malaga University. Methods We designed a cooperation project with The NGO’s ACOES-Honduras and Fe y Alegría-Perú to develop a training experience for students of Medicine and Education. This study is based on the qualitative analysis of the final reports of 16 participants, in which they described their personal and professional experiences. To verify the academic results, the competences of the curriculum have been checked in the sections of the practicum in Education, or the specific ones for Pharmacology in Medicine. In this summary appeared some of them as an example. There are no specifications of names or places of any of the countries or names or references of adults or children. Results In Education six competences (between sixteen) have been pointed out that are enhanced by the context variables in both the organizational and the cultural aspects. In one hand, school functioning may be very similar throughout the world, but the connections between family and the education centre, relationships with students, the influence of the family and the family home, etc., are very different between the experience of the Students with an European lifestyle linked to the "welfare state", consumption, street safety, etc., and rural life and the economic and cultural situation of destinations. Related to the analysis of the medical curricula, it was focused on 27 transversal and 19 specific competences that covered areas of practice and others related to Pharmacology. In the case of transversal competences, around 70% were covered in the activities carried out. Specific competences were covered up to 75%. Volunteer narratives provided an image of the experience that shows the effectiveness of this type of program, both in increasing sensitivity and attention to diversity and in the implementation of "theoretical" training, and the original response to unforeseen situations. Conclusions SL was found to be an effective method to acquire personal and professional competences and skills in the area of pharmacology demand by our present society. Hence we will suggest this methodology in the design of a new subject: “Pharmacotherapeutics in disadvantaged environments”. Most, if not all, of the general views on experience valued those working months with people and marginal contexts very positively. Personal and professional learning is valued as meaningful and profound, affecting the way of understanding the world and its profession: As I tell all my relatives, friends and colleagues "This experience can not be tell you can only live it." (Student)
Keywords: Tecnología educativa; Education; Service-learning; Innovation; Medicine